2011
DOI: 10.1038/oby.2010.328
|View full text |Cite
|
Sign up to set email alerts
|

Household Obesity Prevention: Take Action—a Group‐Randomized Trial

Abstract: The purpose of the present study was to evaluate an intervention to prevent weight gain among households (HHs) in the community. Ninety HHs were randomized to intervention or control group for 1 year. Intervention consisted of six face-to-face group sessions, placement of a television (TV) locking device on all home TVs, and home-based intervention activities. Measures were collected in person at baseline and 1 year. Weight, height, eating behaviors, physical activity (PA), and TV viewing were measured among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(139 citation statements)
references
References 34 publications
(45 reference statements)
7
129
0
3
Order By: Relevance
“…None of the 6 studies reported a significant intervention effect on weightrelated outcomes, whereas 3 reported statistically significant effects of a combined intervention on fruit/vegetable intake 17,21 or sedentary behaviors. 20 No studies reported on clinical outcomes or adverse effects of the interventions.…”
Section: Overall Findings On the Effectiveness Of Home-based Intervenmentioning
confidence: 94%
See 4 more Smart Citations
“…None of the 6 studies reported a significant intervention effect on weightrelated outcomes, whereas 3 reported statistically significant effects of a combined intervention on fruit/vegetable intake 17,21 or sedentary behaviors. 20 No studies reported on clinical outcomes or adverse effects of the interventions.…”
Section: Overall Findings On the Effectiveness Of Home-based Intervenmentioning
confidence: 94%
“…During article screening, we excluded an additional 470 articles. Six studies reporting on home-based interventions (KQ2) were included in this review: 3 home-based combined (diet and PA) intervention studies, [16][17][18] 1 home-based diet intervention study, 19 1 combined home-based study with primary care and consumer health informatics components, 20 and 1 combined home-based study with school and community components (Fig 1). 21 The results of the gray literature search did not yield studies eligible for inclusion in this review.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations